Alan W. Entwistle y Françoise Mallison (comps.). Studies in South Asian Devotional Literature: Research Papers, 1988-1991. Nueva Delhi: Manohar, 1994. xiv, 595 pp. - Lorenzen, David N. (Estudios de Asia y África, 1996)
-